TALENT MANAGEMENT IMPLEMENTATION STRATEGY IN AN EFFORT TO REALIZE SUPERIOR PERFORMANCE - Widiyana Sudrajat; Azhar Affandi; Horas Djulius (Sosiohumaniora, 2023)
Qualitative research was carried out using the Exploratory Research method and the Snowball Sampling interview method with Functional Employees and Officials of the West Java Provincial Civil Service Agency, as key informants. Using the theoretical dimensions of Integrated Talent Management from Berger and Berger (2018) as a knife for analyzing the implementation of talent management, and making a SWOT analysis to choose the right strategy implementation. The results of the study show that effective talent management practices are able to create superior performing employees. To achieve effective talent management, a strategy is needed to strengthen Employee Career Planning, increase Employee Capabilities, build a Talent Mindset culture, obtain full support from the Organization’s Top Leaders, and build a One Apps Talent Management Information Service System. The impact of this research is that it will be able to create opportunities to develop the implementation of effective talent management strategies in public organizations. In an effort to produce superior Employee Performance, it is important for the Organization to align its Organizational Strategy, Culture, Structure and Talent in order to create a world-class West Java Bureaucracy.